Joint Geophysical‐Petrological Modeling on the Ivrea Geophysical Body Beneath Valsesia, Italy: Constraints on the Continental Lower Crust - Mattia Pistone; Luca Ziberna; György Hetényi; Matteo Scarponi; Alberto Zanetti; Othmar Müntener (Geochemistry, Geophysics, Geosystems, 2020)
Abstract One of the few near‐complete continental crustal sections exposed on Earth's surface is the Ivrea‐Verbano Zone (Western Alps, Italy), which is considered as a petro‐geophysical reference of the continental lithosphere. Exposed peridotite slivers embedded in lower crustal rocks at the surface and large density, seismic velocity anomalies of the Ivrea Geophysical Body in the subsurface suggest that mantle‐like rocks are located as shallow as a few kilometers depth, but the actual composition of the rocks producing these anomalies is unknown. Here we investigate how the published seismological and new gravimetric data in the location of Valsesia could be reconciled with petrologic data and models of the Ivrea‐Verbano Zone. We use the Perple_X software to calculate densities and compressional wave velocities for a range of possible deep crustal rock types. We argue that amphibole gabbros (<18 km depth) and pyroxene hornblendites (>18 km depth) provide the best fit to the joint geophysical and petrologic constraints, whereas residual ultramafic rocks and anhydrous gabbros are inconsistent with the existing data. This indicates that the Ivrea Geophysical Body beneath the Valsesia area in the Ivrea‐Verbano Zone preserves the structure of an igneous complex formed during magmatic underplating from the crystallization of hydrous mafic magmas. This would imply melting of a damp mantle source that produced a continental crust of an original thickness of up to ∼48 km in the Permian, of which ∼30 km are exposed at Earth's surface today.